Environmental Guide to the Internet by Carol Briggs-Erickson and Toni Murphy - John Bergman Napp (Issues in Science and Technology Librarianship, 1997)
This article reviews the book Environmental Guide to the Internet, 3rd edition. Rockville, MD: Government Institutes, 1997, by Carol Briggs-Erickson and Toni Murphy.